Analisis Peramalan Pertumbuhan Ekonomi Di Provinsi Maluku Dengan Metode Arima - Tutupoho, Ali; Laitupa, Abdul Azis; Duwila, Ummi (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This study aims to determine the best model of data and results of economic growth forecasts in Maluku Province for the next 5 years. The level of forecasting economic growth in Maluku Province is based on the ARIMA (Autoregressive Integrated Moving Average) method where this method is a periodic series analysis method and known as BoxJenkis which comes from a merger between the Autoregressive (AR) and Moving Average (MA) models developed by George Box and Gwilym Jenkins. The approach used in this study is a quantitative approach, using a quantitative approach, this research will be carried out mathematical calculations that have been simplified using applications to simplify and speed up the calculation process to determine the best ARIMA model in forecasting economic growth. From several model estimates that have been carried out to obtain the best ARIMA model estimation value